Representation of Islam and Shariah by Nigerian print media - Ashimi, Tijani Ahmad (International Islamic University Malaysia, 2013)
Islam is one of the major religion in contemporary Nigeria; it dominates in the north and holds strong numbers in the south western part of the country. This article aims to explore the representation of Islam and its law (Shariah) by media in pluralistic Nigeria. Yet print media with particular reference to some famous Nigerian newspapers are selected for this purpose. However, to achieve the objective of this humble article, analytical method is applied, that is by analyzing the news contents of these papers which might not be in conformity with right teaching of Islam. Indeed, the image of Islam with particular reference to the issue of the Shariah, between the year 2000-2005 in this pluralistic nation (Nigeria) seems to be dogmatic, unfair, intolerant and fanatic. It is important to note that; media in this populous country of Africa has contributed immensely to religious conflict and disharmony. Therefore, the article will also demonstrate some factors behind the attitude of this secular media toward Islam and Shariah in the country. Finally, the article will suggest some solutions to Nigerian print media that if applied, will fetch peace, harmony and unity to Nigerian Society at large.